Adoption of product service systems in health care. - Mittermeyer, Stephan Alexander (Cranfield University, 2017)
Health care systems are constantly challenged to deliver better quality of care at lower cost. Product Services Systems (PSS) aim to output a higher value to a customer, while reducing resource input required to achieve such value and sustainability. In the health care market this could help companies increase their focus on value for the patient, but also for the health care system as such. This focus on value can ultimately help drive down health care cost, which is one of the most pressing issues in health care systems today. The potential of PSS to address some of the major challenges in the health care market was recognised early in PSS research, however adoption in this field is still below expectation. Motivated by the potential of PSS in health care this work aims to explore the current status of adoption as well as drivers and barriers to future adoption in this market and evaluates if and how PSS can be designed and implemented by companies active in this market. This work showed that PSS can be feasible and useful in this sector as they address relevant current challenges. Future changes in the health care market will likely make PSS even more relevant. Certain concepts of PSS are already applied in the market without leveraging the benefits of a fully developed PSS. Limitations in how the value for patients and other market actors is determined and made transparent is a major challenge in the adoption of PSS. An assessment method is proposed to enable companies to evaluate the value generation of their PSS offerings. In addition, a guideline for PSS design is proposed based on results of this work and field observations. This thesis contributes to a better understanding of PSS adoption in health care by investigating mechanisms in the health care market to understand if PSS can be implemented in a useful manner and how PSS can be adopted in health care in the future. As PSS consists of a number of separate concepts that may be used by themselves and also outside a PSS concept, a detailed analysis was performed to evaluate how PSS concepts are already utilized by industry, as such partial implementations may be a good starting point for full PSS adoption. Adoption of a PSS in any industry requires a measure to evaluate the success of a system implementation or the quality of PSS offerings. Given the complex market network in health care, metrics for evaluations have been identified, linking different dimensions of clinical utility to PSS. Those metrics enable companies to assess PSS systems or scenarios, but also enable development teams to focus their PSS design efforts, as those assessment metrics provide a framework for PSS requirements engineering in this market. Based on the results of the work outlined above, design guidelines were defined to support the development process of PSS in health care.
Keywords: Product service systems; PSS; health care; patient value; clinical utility; health care market